Property Prices and Speculative Bubbles : Evidence From Hong Kong SAR - Duenwald, Christoph (IMF Working Papers; Working Paper, 2000)
This paper examines the determinants of residential property prices in Hong Kong SAR during 1980-98. It uses time-series analysis techniques to characterize price developments, establish empirical regularities, and provide measures of the deviations of actual price changes from 'trend.' The analysis suggests that at the peak of the boom, in mid-1997, the level of property prices may have been 40-45 percent above levels suggested by developments in 'fundamentals.' The analysis highlights the role of demand-side factors, and the data are not inconsistent with the notion that the property market may be subject to speculative bubbles.